Redesigned community baby showers to promote infant safe sleep. (December 2020) - Ahlers-Schmidt, Carolyn R; Schunn, Christy; Hervey, Ashley M; Dempsey, Millicent; Blackmon, Sheila; Davis, Brenda; Baker, Trudy; Mayes, Cheryl A; Torres, Maria
Objective: The purpose of this study was to evaluate whether participation in a community event developed using Health Belief Model constructs increased intention to follow the American Academy of Paediatrics Safe Sleep Guidelines for infants. Design: Observational cohort study. Setting: Safe Sleep Community Baby Showers held between Spring 2015 and Spring 2019. Method: Women attending the Safe Sleep Community Baby Showers completed pre- and post-assessments measuring intentions based on constructs derived from the Health Belief Model. Results: Following the Safe Sleep Community Baby Showers, significantly more of the 812 participants demonstrated positive changes in Health Belief Model constructs, including beliefs about severity and susceptibility (infant is at risk, sleeping with infant can cause death, loose blankets can cause death), benefits (putting infant alone, on back in crib will help protect), barriers (infant will [not] choke on back) and self-efficacy (know what to do). Two barriers did not result in significant change: room for crib (cot) in parents' room and able to keep infant warm without blankets. Most reported intention to only place infant supine (99%), in safe sleep locations (97.8%) and to include only safe items (86.2%; all p  < .001). Conclusion: Structuring a community event based on the Health Belief Model resulted in significant increases in participants intending to follow the AAP Safe Sleep Guidelines. Further work is needed to address barriers around blankets and room sharing without bed sharing. Safe Sleep Community Baby Showers can impact Health Belief Model constructs related to the AAP Safe Sleep Recommendations, which may in turn impact behaviour.